A Cephalometric Study of Adult Maharashtra Population - Satpute, Supriya Prashant; More, Swati; Yadav, Aruna Y. (New Frontiers in Medicine and Medical Research Vol. 17, 2021)
The study's goal was to develop cephalometric standards among the adult population of Maharashtra. The participants in this study were 100 males (18-25 years old) and 100 females (18-25 years old) (age between 18-25 years). All of the people in the research had lived in Maharashtra for three to four generations. All of the subjects had class I malocclusion and were growing and developing normally. All of the individuals' maxillary and mandibular arches were perfectly aligned. Nasion (N), Sella (S), Gonion (Go), Pogonion (Po), Gnathion (Gn), Articulare (Ar), and Menton were employed as bony landmarks (Me). Anterior facial height (AFH), posterior facial height (PFH), anterior cranial base (ACB), posterior cranial base (PCB), facial angle, saddle angle, and facial height ratio (FHR) were all examined using these landmarks. Gender dimorphism was shown to be significantly different in the study. The present study establishes surgically useful cephalometric parameters for the diagnosis and treatment planning of orthognathic surgery in adult Maharashtrian population for its practical implementation in the treatment of the facial deformities.